Academic Parenting with VAK Strategy: Improving Reading Skills of 5–6-Year-Old Children through Home Learning Environment Optimization in Indonesia - Cicih Murniasih, Cicih Murniasih; Diah Krisnatuti, Diah Krisnatuti; Yulina Eva Riany, Yulina Eva Riany (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
Parental involvement in children's academic caregiving at home plays a crucial role in their holistic and integrative academic development. This study aims to analyze: (1) descriptive statistics, (2) mean differences, (3) correlations, and (4) the influence of family characteristics, child characteristics, knowledge of the VAK academic parenting strategy, and the quality of the caregiving environment on the reading skills of children aged 5–6 years. The study employed a quasi-experimental one-group pre-test and post-test design. The participants were 100 stay-at-home mothers residing in Ciputat, South Tangerang, from intact families, with children aged 5–6 years enrolled in early childhood education programs. All mothers were aged 25–40 years, held at least a high school diploma or equivalent, and were not employed. The results of the Paired Sample T-Test indicated significant differences between pre-test and post-test scores, showing increases in all measured variables. Regression analysis revealed that the mother’s age negatively affected children's reading abilities, while the child’s age, gender (with girls performing better), maternal knowledge of the VAK strategy, and the quality of the caregiving environment had significant positive effects. These findings highlight the effectiveness of training in the VAK academic parenting strategy, particularly in helping older mothers transform information into new or improved knowledge that can be applied in caregiving practices at home. A key limitation of this study is its reliance on a single geographic area and a relatively homogeneous sample, which may affect the generalizability of the findings. Future research is recommended to include more diverse participant backgrounds and longitudinal tracking to assess the long-term impact of academic parenting strategies.